"I'm the Momma": Using photo-elicitation to understand matrilineal influence on family food choice - Sharkey Joseph R; Johnson Cassandra M; McIntosh Alex W; Dean Wesley R (BMC, 2010)
Abstract Background Many complex and subtle aspects relating to mothers and food choice are not well understood. Mothers play a primary role in their children's food choices, but research has not specifically examined how matrilineal family members who do not reside in the same household, such as a mother's mother, aunt, or grandmother, influence the current family's food choices. Methods Seven participants were recruited from the Household Food Inventory (HFI) Study in the Bryan/College Station, Texas. All participants completed an in-depth interview, photographed food-related activities, and discussed photographs in a follow-up in-depth interview. Interviews were transcribed verbatim from audio recordings. Transcripts were analyzed using several qualitative approaches including grounded theory to identify themes and subthemes. Results Participants discussed the following themes relating to the influence of their mother or other female relation (Mom) on their families' food choices: Relationship with Mom, Just like Mom, 'Kinda' like Mom, Different than Mom, and Mom's Influence on Children's Food Choices. Overall, participants used the photographs to illustrate how they were similar or different to their mothers, or other female family member, as well as how their mothers either supported or undermined control over their children's food choices. The "Mom effect" or matrilineal influence of mothers, aunts, and grandmothers on a mother's food choices was omnipresent, even though Mom was no longer living with the participants. Conclusions We found a matrilineal influence to have a residual and persistent influence on a family's food choices. This finding may be helpful for understanding the contextual elements of food choice and explaining why it is sometimes difficult to change mothers' food habits.